THE NEED FOR COLLEGE COURSES IN INTERNAL AUDITING. - Cunningham, Earle H. (The Accounting Review, 1955)
This article focuses on the need for college courses in internal auditing. The need for college courses in internal auditing is a much debated subject. While college educators hesitate to add special courses to an already crowded curriculum, those interested in the field of internal auditing see the need for a higher grade of training for the internal auditor than is currently available. This need stems, primarily, from the broader responsibilities assigned to the internal auditor, and the increasing range of services he is required to render. Each company making use of internal auditing created this function in accordance with its own concepts and particular needs. In those cases where all operations were established at one location, were controlled by one accounting system, and were subject to close management supervision, the clerical type of internal auditing generally prevailed. While normal management problems have been constantly increasing over the years, World War II brought a pyramid of new problems.